Prevention of doxorubicin-induced cardiomyopathy using targeted MaFGF mediated by nanoparticles combined with ultrasound-targeted MB destruction - Tian XQ (Dove Medical Press, 2017)
Xin-Qiao Tian,1,2,* Xian-Wei Ni,3,* He-Lin Xu,2,* Lei Zheng,4 De-Li ZhuGe,2 Bin Chen,4 Cui-Tao Lu,2 Jian-Jun Yuan,1 Ying-Zheng Zhao2 1Department of Ultrasonography, Henan Provincial People’s Hospital (People’s Hospital of Zhengzhou University), Zhengzhou, 2Department of Pharmacology, College of Pharmaceutical Sciences, Wenzhou Medical University, 3Department of Ultrasonography, The Second Affiliated Hospital of Wenzhou Medical University, 4Department of Ultrasonography, The First Affiliated Hospital of Wenzhou Medical University, Wenzhou, Zhejiang, China *These authors contributed equally to this work Abstract: The present study seeks to observe the preventive effects of doxorubicin-induced cardiomyopathy (DOX-CM) in rats using targeted non-mitogenic acidic fibroblast growth factor (MaFGF) mediated by nanoparticles (NP) combined with ultrasound-targeted MB destruction (UTMD). DOX-CM rats were induced by intraperitoneally injected doxorubicin. Six weeks after intervention, the indices from the transthoracic echocardiography and velocity vector imaging showed that the left ventricular function in the MaFGF-loaded NP (MaFGF-NP) + UTMD group was significantly improved compared with the DOX-CM group. The increased malondialdehyde and decreased superoxide dismutase were observed in the DOX-CM group, while a significant increase in superoxide dismutase and a decrease in malondialdehyde were detected in the groups treated with MaFGF-NP + UTMD. From the Masson staining, the MaFGF-NP + UTMD group showed a significant difference from the DOX-CM group. The cardiac collagen volume fraction and the ratio of the perivascular collagen area to the luminal area number of terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labelling positive cells in the MaFGF-NP + UTMD group decreased to 8.9%, 0.55-fold, compared with the DOX-CM group (26.5%, 1.7-fold). From terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nick end labelling staining, the results showed the strongest inhibition of apoptosis progress in MaFGF-NP + UTMD group. The immunohistochemical staining of the TGF-β1 in MaFGF-NP + UTMD group reached 3.6%, which was much lower than that of the DOX-CM group (12.6%). These results confirmed that the abnormalities, including left ventricular dysfunction, myocardial fibrosis, cardiomyocytes apoptosis and oxidative stress, could be suppressed by twice weekly MaFGF treatments for 6 consecutive weeks (free MaFGF or MaFGF-NP+/UTMD), with the strongest improvements observed in the MaFGF-NP + UTMD group. Western blot analyses of the heart tissue further revealed the highest pAkt levels, highest anti-apoptosis protein (Bcl-2) levels and strongest reduction in proapoptosis protein (Bax) levels in the MaFGF-NP + UTMD group. This study confirmed the preventive effects of DOX-CM in the rats with MaFGF-NP and UTMD by retarding myocardial fibrosis, inhibiting oxidative stress, and decreasing cardiomyocyte apoptosis. Keywords: doxorubicin-induced cardiomyopathy, MaFGF, UTMD, MaFGF-loaded